Sex hormones and diets rich in polyunsaturated ω-6/ω-3 fatty acids modify microbiota distinctly in a mouse model of Alzheimer’s disease - Lara Ordoñez-Gutierrez; Francisco Wandosell (Gut Microbiome, 2025)
There is considerable data suggesting that the gut microbiota (GM) contributes to health and regulates host immunity and influences brain function, findings with implications for neurodegenerative diseases, such as Alzheimer’s Disease (AD).